2006
DOI: 10.1515/cclm.2006.207
|View full text |Cite
|
Sign up to set email alerts
|

A long and winding road: defining the biological role and clinical importance of paraoxonases

Abstract: Paraoxonase-1 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 76 publications
1
83
0
1
Order By: Relevance
“…Early, in vitro studies suggested that purified PON1 and HDL-associated PON1 could protect LDL from oxidation (Mackness et al 2003), although these conclusions were questioned in subsequent reports (James 2006). However, studies from several animal models (James 2006) have provided much stronger support for the conclusion that PON1 protects against atherosclerotic disease by a process that involves reduction of oxidative stress.…”
Section: Pon1 As An Antioxidantmentioning
confidence: 99%
See 3 more Smart Citations
“…Early, in vitro studies suggested that purified PON1 and HDL-associated PON1 could protect LDL from oxidation (Mackness et al 2003), although these conclusions were questioned in subsequent reports (James 2006). However, studies from several animal models (James 2006) have provided much stronger support for the conclusion that PON1 protects against atherosclerotic disease by a process that involves reduction of oxidative stress.…”
Section: Pon1 As An Antioxidantmentioning
confidence: 99%
“…However, studies from several animal models (James 2006) have provided much stronger support for the conclusion that PON1 protects against atherosclerotic disease by a process that involves reduction of oxidative stress. Thus PON1 knockout in mice was associated with a significant increase in the development of atherosclerotic lesions, whilst HDL from such mice were less able to protect LDL from oxidation (Shih et al 1998(Shih et al , 2000.…”
Section: Pon1 As An Antioxidantmentioning
confidence: 99%
See 2 more Smart Citations
“…Human paraoxonase 1 (PON1) is a calcium-dependent serum enzyme that is found in association with HDL (1). PON1 has a variety of substrates and has been found to have multiple polymorphisms in both the coding sequence (L55M, Q192R) and in the noncoding sequence (2).…”
mentioning
confidence: 99%